"Kneel, compañero:" Monsignor Quixote's Sacramental Adventure. (25th March 2021) - Comerford, Peter J.
Abstract: Graham Greene's Monsignor Quixote illustrates an ecclesiology of friendship through the title character's relationship with Sancho. Quixote is depicted as a holy fool, who is able to bring his companero back to the faith by his open mutual mediation with him. Greene has not strayed from orthodoxy, but has developed his theology compared to his earlier novels